2020
DOI: 10.1016/j.jaut.2020.102511
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 receptor blocking with intravenous tocilizumab in COVID-19 severe acute respiratory distress syndrome: A retrospective case-control survival analysis of 128 patients

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 35 publications
0
91
1
1
Order By: Relevance
“…For example, Optimal COVID-19 infection management with TCZ is not achieved during hyperglycaemia in both diabetic and non-diabetic patients that TCZ administration neither decreases IL-6 levels nor attenuates risk of severe outcomes (55). Similarly, the use of TCZ fails to decrease the mortality rate at 30 days of patients with severe COVID-19 acute respiratory distress syndrome with hyperinflammation, after correction for pre-existing comorbidities and the need for respiratory support (56). In addition, adverse reactions of TCZ in other long-course treatments need to be noted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Optimal COVID-19 infection management with TCZ is not achieved during hyperglycaemia in both diabetic and non-diabetic patients that TCZ administration neither decreases IL-6 levels nor attenuates risk of severe outcomes (55). Similarly, the use of TCZ fails to decrease the mortality rate at 30 days of patients with severe COVID-19 acute respiratory distress syndrome with hyperinflammation, after correction for pre-existing comorbidities and the need for respiratory support (56). In addition, adverse reactions of TCZ in other long-course treatments need to be noted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several retrospective case-control studies on the use of tocilizumab in COVID-19 have been published ( 121 126 ), of which a majority reported a favorable outcome of tocilizumab treatment compared to controls. Of these, Campochiaro et al and Canziani et al did not find a statistically reduced mortality in tocilizumab treated patients, although both studies showed a respective trend ( 121 , 122 ) additionally, tocilizumab treated patients required invasive ventilation statistically less frequently than controls ( 122 ). In line with this observation the outcomes of several studies suggest that patients may benefit most from tocilizumab if given before invasive ventilation ( 125 , 127 ).…”
Section: Should We Use Dmards For the Therapy Of Covid-19?mentioning
confidence: 92%
“…The total (random effects) synthesizes data from the 16 individual case-control studies. significance (Colaneri et al, 2020;Roumier et al, 2020;Guaraldi et al, 2020;Canziani et al, 2020) (Table S1). Only one study (Colaneri et al, 2020) provided both baseline and post-treatment values for biomarkers such as IL-6, CRP, lymphocytes, neutrophils, ALT etc.…”
Section: Figurementioning
confidence: 99%
“…5) and the number of patients in the meta-analysis exceeded the 392 required total case and control patients to statistically detect the difference in mortality rate. Some studies also secondarily investigated the rate of ICU admission with nine finding a lower rate with TCZ vs SOC and four having statistical significance (Colaneri et al, 2020;Roumier et al, 2020;Guaraldi et al, 2020;Canziani et al, 2020) (Table S1). Although the value of any single controlled clinical study does not hold definitive proof of efficacy, the consistent positive trend and statistical significance from the combined data in this analysis corroborates TCZ's potential positive effects.…”
Section: Mortalitiesmentioning
confidence: 99%